'Becoming-with bees': generating affect and response-abilities with the dying bees in early childhood education. Issue 3 (3rd May 2020) - Weldemariam, Kassahun
ABSTRACT: Engaging young children in sustainability challenges poses a pedagogical dilemma to the field of early childhood education. Using species extinction as an exemplary sustainability challenge, this study explores the pedagogical possibilities to engage young children with the potentially cataclysmic death of the bee. The study is framed within a posthumanist framework and draws ideas from post-qualitative research orientation. The study is empirically anchored to a narrative emerging from a staged theatrical performance of child-bee assemblage that enacts the collective agency of 'bee-ness'. Enabling possibilities of 'becoming-with the bees', the performance lends itself to triggering response-abilities and forming of relationships and thus a concomitant emotional affective response to the death of bees. The article suggests alternative directions for a sustainability pedagogy in early childhood education that represent a shift from loving, caring and preserving nature as an object outside ourselves, towards a perspective of 'becoming-with-nature', which considers humans as part of/entangled with nature.